Peranan Silek Moncak dalam Acara Manjalang Niniak Mamak di Nagari Muaro Paiti Kecamatan Kapur IX - Selsi Efrima Yuni; Desfiarni Desfiarni (Institut Nalanda, 2023)
This study aims to describe and analyze the role of Silek Moncak in the Manjalang Niniak Mamak event in Nagai Muaro Paiti, Kapur IX District, Fifty Cities Regency. This type of research is qualitative research using descriptive methods of analysis. Research instruments are researchers themselves and are assisted by supporting instruments such as stationery and cameras. The data in this study used primary data and secondary data. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps of analyzing data are data collection, describing data and inferring data. The results showed that the Manjalang Niniak Mamak event in Nagari Muaro Paiti Kec. Kapur IX Kab. Fifty Cities is an event that grows and develops in society from the past until now. The Manjalang Niniak Mamak event is an event that is held once a year, which is 3 days after Eid al-Fitr with the aim of strengthening the relationship between Niniak Mamak and kamanakan. Silek Moncak's performance in welcoming the Eid al-Fitr celebration at Nagari Muaro Paiti. At the event of approaching ninik mamak Silek Moncak, one of the arts that is always displayed because the role of Silek Moncak in the Manjalang Niniak Mamak event has an important role, because in the Manjalang Niniak Mamak Silek Moncak event reflects the behavior of the Nagari Muaro Paiti community who maintain a close relationship, between kamanakan and ninik mamak and fellow communities through the introduction of Silek Moncak. Silek Moncak also reflects the strength, politeness, and behavior of the community (togetherness, mutual respect and honesty) in Nagari Muaro Paiti. Silek Moncak is played by two men, namely Dubalang, the age for those who play Silek Moncak is not determined because the Dubalang of each tribe is of different age.